1991
DOI: 10.1530/acta.0.1250291
|View full text |Cite
|
Sign up to set email alerts
|

Circulating thyroglobulin measurements by homologous radioimmunoassay in dogs with thyroid carcinoma

Abstract: Circulating thyroglobulin was measured in 20 dogs with thyroid cancer, using a homologous polyclonal radioimmunoassay. Plasma Tg levels exceeded the normal range in 14 (70%) dogs, and ranged from 6 to 2902 \g=m\g/l(median 608). Plasma Tg levels tended to decrease from follicular carcinomas to solid-follicular carcinomas, to solid carcinomas (p<0.05). Plasma Tg levels were also higher in scintigraphically hot tumours than in cold ones. Other relationships between circulating Tg and clinical, pathological, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…1). According to the radiotracer concentration (uptake) in the gammagraphy study, (Verschueren et al, 1991) tumours were classified as hot (high uptake compared to the contralateral lobe and the salivary glands that are inhibited), cold (low uptake with respect to the contralateral lobe and salivary glands, with normal uptake), or normal-uptake (both thyroid lobes uptake and the salivary glands uptake are equals). Dogs that presented any lymph node affected with local invasion or distal metastasis were excluded from the experiment.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations
“…1). According to the radiotracer concentration (uptake) in the gammagraphy study, (Verschueren et al, 1991) tumours were classified as hot (high uptake compared to the contralateral lobe and the salivary glands that are inhibited), cold (low uptake with respect to the contralateral lobe and salivary glands, with normal uptake), or normal-uptake (both thyroid lobes uptake and the salivary glands uptake are equals). Dogs that presented any lymph node affected with local invasion or distal metastasis were excluded from the experiment.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…There are few reports regarding the relation among thyroid carcinoma functionality and/or TC histopathology. Regarding the functional characteristics, Verschueren et al (1991) reported that the greater the undifferentiated thyroid carcinoma profile, the less binding sites for TSH and 99m Tc uptake were found. Similarly, a greater expression of thyroglobulin and TSH-R was found in follicular cells within the carcinoma tissue where the remaining thyroid follicle architecture was found.…”
Section: Recurrence and Survival Timementioning
confidence: 99%
See 2 more Smart Citations